Six weeks of N-acetylcysteine antioxidant in drinking water decreases pathological fiber branching in MDX mouse dystrophic fast-twitch skeletal muscle - Redwan, Asma; Kiriaev, Leonit; Kueh, Sindy; Morley, John W.; Houweling, Peter; Perry, Ben D.; Head, Stewart I. (Frontiers in Physiology, 2023)
Introduction: It has been proposed that an increased susceptivity to oxidative stress caused by the absence of the protein dystrophin from the inner surface of the sarcolemma is a trigger of skeletal muscle necrosis in the destructive dystrophin deficient muscular dystrophies. Here we use the mdx mouse model of human Duchenne Muscular Dystrophy to test the hypothesis that adding the antioxidant NAC at 2% to drinking water for six weeks will treat the inflammatory phase of the dystrophic process and reduce pathological muscle fiber branching and splitting resulting in a reduction of mass in mdx fast-twitch EDL muscles. Methods: Animal weight and water intake was recorded during the six weeks when 2% NAC was added to the drinking water. Post NAC treatment animals were euthanised and the EDL muscles dissected out and placed in an organ bath where the muscle was attached to a force transducer to measure contractile properties and susceptibility to force loss from eccentric contractions. After the contractile measurements had been made the EDL muscle was blotted and weighed. In order to assess the degree of pathological fiber branching mdx EDL muscles were treated with collagenase to release single fibers. For counting and morphological analysis single EDL mdx skeletal muscle fibers were viewed under high magnification on an inverted microscope. Results: During the six-week treatment phase NAC reduced body weight gain in three- to nine-week-old mdx and littermate control mice without effecting fluid intake. NAC treatment also significantly reduced the mdx EDL muscle mass and abnormal fiber branching and splitting. Discussion: We propose chronic NAC treatment reduces the inflammatory response and degenerative cycles in the mdx dystrophic EDL muscles resulting in a reduction in the number of complexed branched fibers reported to be responsible for the dystrophic EDL muscle hypertrophy.